A Horizontal Mesiodens in a Child Buried at Hank's Site (41RB109), a Prehistoric Plains Village Site in the Texas Panhandle - Cory J. Broehm; Lisa B. Hunter; Douglas K. Boyd (Dental Anthropology Association, 2011)
The mesiodens is the most common kind of supernumerary tooth; it is found in the midline of the maxilla. Horizontal orientation is the least common, accounting for about 6% of cases. During osteological analysis of the skeleton of a 3 to 5 year old child recovered from Hank's site (41RB109) in the northern Texas panhandle, an impacted horizontal, conical mesiodens was identified. The skeleton dates to the Plains Village period, ca. A.D. 1,200 to 1,500, when village-based peoples practiced a mixed hunter-gatherer/horticulture subsistence. This mesiodens is located in the right maxilla, just lateral to the midline of the hard palate and parallel to the intermaxillary suture. The root projects ventrally and protrudes through the external alveolar bone between the central incisors. The crown is conical. Although sometimes found in association with certain congenital disorders, the mesiodens appears to be idiopathic in this case. While possibly painful due to its proximity to the nasopalatine nerve, no sequela from the tooth growth and impaction are evident.